The Perceptions of Vocational School Students of Video Animation-Based Learning Media to Operate Lathes in Distance Learning - Kusuma, Wahyu Mustafa; Sudira, Putu; Hasibuan, Mhd Akbar; Daryono, Rihab Wit (Journal of Education Technology, 2021)
SMK has the challenge of implementing meaningful distance learning using animated video media according to student perceptions. However, students' perceptions about the use of animated video media in distance learning are not yet known. This study aims to measure the perceptions of Mechanical Engineering Vocational School students about the use of animated video media for the development of skills to operate a lathe in distance learning. The research subjects consisted of 73 students of Mechanical Engineering Vocational Schools. The data collection technique used a questionnaire. The media feasibility test was carried out by two material and media experts. This study used quantitative descriptive statistical analysis methods, t-test, and One-Way ANOVA with post-hoc advanced tests, namely the Dunnett C and Tukey test to determine differences in students' perceptions of assessment. The results of the media feasibility validation by material experts were 81.875% and media experts 90.625% were in the very feasible category. The assessment of the feasibility of the media by students was 83.714% in the very feasible category. So, that there was no significant difference between male and female students in the assessment of distance learning animated video media.